IMPLEMENTASI PROGRAM KURIKULUM TINGKAT SATUAN PENDIDIKAN DI DAERAH STUDI KASUS SMP 2 NGRAMBE KECAMATAN NGRAMBE KABUPATEN NGAWI JAWA TIMUR - , IVON DIONA AGA M, Dra. Ambar Teguh Suliatiyani, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Education is one of the human rights of the most fundamental. An obligation for the state to build a community education in the context of national life, as stated in the 1945 Constitution, paragraph 4. Implementation of regional autonomy led to the decentralization of education in an effort to boost the development of education, then the school year 2006/2007 the government began to implement unit level education curriculum (SBC) that provides the broadest authority for schools to make their own curriculum in accordance with the ability to be able to bring seeds later in the day. Implementation of the policy is defined as any action in order to achieve policy goals and objectives that have been formulated while the curriculum is a set of plans and arrangements regarding the purpose, content, and teaching materials and methods used to guide the implementation of learning activities to achieve specific educationalgoals. The data analysis technique used in this study is an interactive analysis technique is a qualitative data analysis technique that consists of three flow activities, namely (1) data reduction, (2) the presentation of the data, and (3) concluding that occur simultaneously (Milen and Huberman, 1992: 16). Results of this study indicate that in implementing the curriculum or the Education Unit at SMP Negeri 2 Ngrambe not optimal because there are still problems such as lack of social,